2016
DOI: 10.1128/jvi.00126-16
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Dysregulates Host Histone Deacetylase 1 That Inhibits Viral Infection in Lung Epithelial Cells

Abstract: Viruses dysregulate the host factors that inhibit virus infection. Here, we demonstrate that human enzyme, histone deacetylase 1 (HDAC1) is a new class of host factor that inhibits influenza A virus (IAV) infection, and IAV dysregulates HDAC1 to efficiently replicate in epithelial cells. A time-dependent decrease in HDAC1 polypeptide level was observed in IAV-infected cells, reducing to <50% by 24 h of infection. A further depletion (97%) of HDAC1 expression by RNA interference increased the IAV growth kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 53 publications
10
62
2
Order By: Relevance
“…This indicates that HDAC11 siRNA does contribute to further reducing the HDAC11 mRNA level during the course of infection and, consequently, to IAV proliferation. The extent of increase in virus release from HDAC11‐depleted cells was larger than about 3.0‐, 4.0‐, and 6.0‐fold increase from HDAC 1‐, 2‐, and 6‐depleted cells, respectively, we observed earlier (Husain & Cheung, ; Nagesh et al, ; Nagesh & Husain, ). One of the possible explanations for this could be that, compared with the Classes I and II HDACs, HDAC11 is evolutionarily the least evolved HDAC and has retained the original structure as well as function assigned to its common ancestral gene(s) by nature.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…This indicates that HDAC11 siRNA does contribute to further reducing the HDAC11 mRNA level during the course of infection and, consequently, to IAV proliferation. The extent of increase in virus release from HDAC11‐depleted cells was larger than about 3.0‐, 4.0‐, and 6.0‐fold increase from HDAC 1‐, 2‐, and 6‐depleted cells, respectively, we observed earlier (Husain & Cheung, ; Nagesh et al, ; Nagesh & Husain, ). One of the possible explanations for this could be that, compared with the Classes I and II HDACs, HDAC11 is evolutionarily the least evolved HDAC and has retained the original structure as well as function assigned to its common ancestral gene(s) by nature.…”
Section: Discussionsupporting
confidence: 59%
“…The data presented above demonstrating the noticeably significant proliferation of IAV in HDAC11‐depleted cells and a profound downregulation of HDAC11 transcript level in infected cells—a sign of viral antagonism of HDAC11—indicated that, like HDAC 1 and 2 (Nagesh et al, ; Nagesh & Husain, ), HDAC11 is part of the host defences. Therefore, we next investigated the role of HDAC11 in IAV‐mediated induction of host IFN response.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Interestingly, 41 of the 199 druggable cellular factors were shown to be implicated in IAV infection (Table S2) [10,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,...…”
Section: Combination Of Various Omics Techniques Identifies Potentmentioning
confidence: 99%